KESIAPAN PETUGAS PUSKESMAS RENDANG DALAM MENGIMPLEMENTASIKAN PROGRAM JAMINAN KESEHATAN NASIONAL(JKN) KABUPATEN KARANGASEM BALI 2014 - Darma Putra Suryapranata; Nyoman Sutarsa (DiscoverSys Inc., 2015)
Efforts to health insurance program for the community actually were pioneered by the government by some forms of social security in the health sector. In 2004, Issued the act no.40 about national social security system that regulates about the implementation of national health insurance (NHI) through a social insurance agent. The purpose of this research is to find readiness of primary health care officers rendang karangasem to implement it. Phenomenology design is used in descriptive qualitative research. Number of samples were 5 people, With the criteria of accuracy and validity of information obtained. This research were done for about 2 months, started from Februari until March 2014. Based on the result obtained discerned from the aspect of quality and quantity, from the perspective of puskesmas officers factors is considered sufficient human resources and infrastructure. Human resources is main pillars supporting areas and locomotion the organization. Good human resources, will become a strong pillars in implementing it. The building and an ambulance as infrastructure supporting the program implementation puskesmas and of these, is considered to be is quite sufficient from the perspective of puskesmas officers rendang.